Modern Science and the Capriciousness of Nature - Rogers, K. author. aut Link
VII, 241 p.
Keywords: This book questions the way that modern science and technology are considered able to liberate society from the erratic forces of nature. Modern science is implicated in a gamble on a technological society that will replace the natural world with a 'better' one. The author questions the rationality of this gamble and its implications for our lives.